Legalization Of Abortion Against Victims Of Rape Crimes Viewed From Victimology Perspective - Elvandari, Siska (UI Scholars Hub, 2020)
One of human rights guaranteed and protected in the 1945 Constitution is the right to live and maintain life, stated in Article 28 A of the 1945 Constitution. The right to live and maintain life is the highest right that is inherent in human beings as the subject of law since humans were born to death in the world. The right to live and maintain life is not only inherent in human beings who have been born, but also in humans or children who are still in the womb, stated in Article II of the Civil Code that